Using guidelines to improve quality in software nonfunctional attributes - Hneif, M.; Lee, S.P. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Software development aims to produce software systems that satisfy two requirement categories: functional and quality. One aspect of software quality is nonfunctional attributes (NFAs), such as security, performance, and availability. Software engineers can meet NFA requirements by applying suitable guidelines during software development. However, this process is complicated by the different effects of different guidelines on NFA quality and the relationships among the guidelines themselves. Thus, finding a suitable set of guidelines is not straightforward. This article introduces a step-by-step approach that gives software engineers a suitable guideline set to apply to improve NFA quality during the software development life cycle. The approach manages the effects different guidelines have on both the attributes and the relationships among the guidelines.